(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Environmental issues now occupy a significant place in academic discourse and activism alike. Situation of India with regard to environmental crisis and resource depletion is deepening in the wake of rapid changes brought about by the new regime of economic liberalization and penetration of transnationals. However, few geographers have been able to take a holistic view of environment. Vulnerability is the key to our understanding that attempts to break from all-too technocratic agenda that have characterised relationship between human societies and their environments over previous centuries. There is a serious lack of integrated techniques and approaches to study vulnerable environment. There is a need to identify challenges and opportunities for improving human well-being through vulnerability analysis of different ecosystems and community groups. While application of GIS and remotely sensed data can make a world of difference, few seem to have undertaken meaningful research using this important tool. There is a dearth of empirical studies evaluating the impact of the current phase of liberalization and globalization on the environment and resources both at national and local levels.